Herbal Multivitamins and Probiotic Synergy as a Sustainable Alternative to Antibiotics: Enhancing KUB Chicken Performance During the Grower Period - Kamil, A. N.; Priyambodo, D.; Ayuningtyas, G.; Sembada, P.; Kamil, Aida Nadira; Priyambodo, Danang; Ayuningtyas, Gilang (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
Antibiotics continue to pose a significant challenge within animal husbandry, as they can lead to residual antibiotics in poultry. Meanwhile, probiotics and herbs have been explored as potential alternative antibiotics to replace their role and promote more sustainable chicken production. The study aims to substitute antibiotics in poultry farming to produce high-performance KUB chickens during the grower period. The research design employed a complete randomized design to assess the variation in production performance of 2,196 KUB chickens (male and female, aged between six to ten weeks), with the treatment groups receiving herbal multivitamins (multivitamins, curcuma extract, amino acids, and electrolytes) and probiotics (containing Lactobacillus sp., Saccharomyces, and Rhodopseudomonas palustris). The treatments in this study incorporated herbal multivitamins and probiotics, specifically: P0, control (antibiotics); P1, herbal multivitamins; and P2, herbal multivitamins and probiotics. The study was conducted over five weeks, during which the observed variables included feed consumption, body weight, body weight gain, feed conversion ratio, and depletion rate. The findings revealed that the provision of herbal multivitamins and probiotics substantially influenced the performance of KUB chickens during the grower period. The findings indicated that combining herbal multivitamins and probiotics yielded superior performance outcomes (body weight = 805,65 ± 0,92a; FCR = 3,46 ± 0,00 B) compared to other treatments, which could be a substitute for antibiotics in raising KUB chickens.